Improvisation : methods and techniques for music therapy clinicians, educators and students - Wigram, Tony (J. Kingsley Publishers, 2004)
Improvisation plays a key role in the toolbox of the music therapist. Tony Wigram's practical and comprehensive guide and CD will prove indispensable to students, teachers, therapists and musicians as a book of musical techniques and therapeutic methods. Beginning with an overview of developing, teaching and analysing the skills of improvisation, Wigram describes techniques ranging from warming up to mirroring, rhythmic grounding, containing and holding. With specific sections on piano improvisation, chordal and 2-, 3- and 4- note improvisation are covered, in addition to advanced skills such.